Dampak Overthinking dan Pencegahannya Menurut Muhammad Quraish Shihab Studi Surah Al-Hujurat Ayat 12 - Utami, Tika Setia; Andy, Safria; Datmi, Muhammad Akbar Rosyidi (Ikatan Da'i Indonesia, 2023)
Overthinking in kbbi is too much time to think about things in a detrimental way and Overthinking can be in the form of khwatir, Overthinking in the Islamic perspective a special form of feeling of fear. The fear that arises will develop greater if it is accompanied by feelings of alertness, anxiety, the presence of certain fantasies and emotions. Overthinking can be caused because it is not yet fully human to have tawakkal skills and depend only on God, Overthinking can also waste energy from thinking about things in an excessive way. Overthinking makes a person think of fears that do not necessarily occur and then cause anxiety in the individual. Overthinking is not a trivial matter, to be honest, there are no trivial problems, everything must be addressed immediately. The purpose of the study is to know how overthinking is understood, knowing the biography of Muhammad Quraish Shihab and Tafsir Al-Misbah in social conditions and knowing Overthinking and its prevention according to Muhammad Quraish Shihab in Quran Surah Al-Hujurat verse 12.This type of research uses library research, in literature research in collecting data through the analysis of books and books that are related and have a relationship in supporting research and also writing looking at conditions regarding overthinking. Overthinking leads to bad thinking because basically all is well that in the Tafsir surah Al-hujurat verse 12 it is explained, O people of faith, stay away from the earnest efforts of many of the conjectures i.e. prejudice against human beings who do not have adequate indicators, indeed some of the conjectures that do not have indicators are sins.